Load transfer mechanisms in geotextile-reinforced embankments overlying voids: Numerical approach and design. Issue 3 (June 2016) - Villard, Pascal; Huckert, Audrey; Briançon, Laurent
Abstract: A numerical model was used to investigate the mechanical behaviour of granular embankments reinforced by geosynthetics in areas prone to subsidence and to overcome the shortcomings of the current design methods. The ability of the numerical model to consider the load transfer mechanisms and the deflection of the geosynthetic was established by comparison with experimental data. By testing two numerical processes, it was demonstrated that the cavity opening modes have a great influence on the shape of the load distribution transmitted to the geosynthetic sheet above the cavity and on the expansion mechanisms of the soil. An approximate conical load distribution seems well adapted when considering a progressive cavity diameter opening process, whereas an inverted load distribution seems more suitable for a gradual settlement process. In both cases, the intensity of the load transfer mechanism can be approached by the Terzaghi's formulation using an appropriate value for the ratio between the horizontal and vertical stresses. Finally, recommendations based on the experimental and numerical results are proposed to promote a better design of such structures.